2019
DOI: 10.1097/ruq.0000000000000462
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Assessment of Muscular Stiffness in Children With Chronic Kidney Disease Using Acoustic Radiation Force Impulse Ultrasound Elastography

Abstract: The aim of this study was to evaluate the feasibility of quantitative analysis of muscle stiffness in the rectus femoris muscle (RFM) by acoustic radiation force impulse (ARFI) ultrasound elastography in children with chronic kidney disease (CKD). Twenty-three children with CKD and 22 healthy children participated in the study in our radiology department. The strength of each CKD group and healthy group participants' tight extensors was assessed by a physiatrist using a handheld dynamometer. Acoustic radiation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…It has been used mainly in the determination of hepatic fibrosis and cirrhosis in chronic viral hepatitis and displays a good correlation with the degree of liver fibrosis[ 92 , 93 ]. In recent years, the ARFI technique has also been applied to other organs, such as the muscles[ 94 ], prostate[ 95 ], and breast[ 96 ]. Fibrosis is the core process of the progression of CKD and this method has also been evaluated in this scenario.…”
Section: Methods Of Assessment Of Renal Functionmentioning
confidence: 99%
“…It has been used mainly in the determination of hepatic fibrosis and cirrhosis in chronic viral hepatitis and displays a good correlation with the degree of liver fibrosis[ 92 , 93 ]. In recent years, the ARFI technique has also been applied to other organs, such as the muscles[ 94 ], prostate[ 95 ], and breast[ 96 ]. Fibrosis is the core process of the progression of CKD and this method has also been evaluated in this scenario.…”
Section: Methods Of Assessment Of Renal Functionmentioning
confidence: 99%
“…One responsiveness study used the Aixplorer on 9 children with CP, revealing decreased shear modulus in gastrocnemius lateralis after botulinum Toxin-A injection (Brandenburg et al 2018). For the Acuson, there are two construct validity studies that report a lower shear wave velocity in the rectus femoris in children with chronic kidney disease (Bekci et al 2019) and a higher shear wave velocity in the gastrocnemius medialis in children with CP, compared with typically developing children (Bilgici and Bekci 2018). One concurrent validity study reported a positive correlation between the shear wave velocity reported by the Acuson and the Modified Ashworth Scale in 16 children with CP (Bilgici and Bekci 2018).…”
Section: Use Of the Included Devices In Childrenmentioning
confidence: 99%
“…One concurrent validity study reported a positive correlation between the shear wave velocity reported by the Acuson and the Modified Ashworth Scale in 16 children with CP (Bilgici and Bekci 2018). Use of the Acuson was reported in two negative inter-rater reliability studies in children with chronic kidney disease (Bekci et al 2019) or CP (Bilgici et al 2017). One responsiveness study used the Acuson with 12 children with CP, revealing decreased shear wave velocity in the gastrocnemius medialis after botulinum toxin-A injection (Bilgici et al 2017).…”
Section: Use Of the Included Devices In Childrenmentioning
confidence: 99%